Metal and metalloid biorecovery using fungi - Liang, Xinjin (Microb Biotechnol, 2017)
Bioleaching is a proven bioprocess for metal recovery by solution from solid matrices, while a bioprecipitation or biomineralization approach is of potential for biorecovery from solution. Fungi can directly and indirectly mediate the formation of many kinds of minerals, including oxides, phosphates, carbonates and oxalates, as well as elemental forms of metals and metalloids such as Ag, Se and Te. Fungal capabilities may offer a potentially useful contribution to biotechnological and physico‐chemical methods for metal recovery.[Image: see text]